2021
DOI: 10.1093/jpepsy/jsab021
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impacts on Families of Color and Families of Children With Asthma

Abstract: Objective This cross-sectional study quantified differences in (a) social determinants of health (SDOH) and perceived changes in SDOH during the 2019 novel coronavirus (COVID-19) pandemic and (b) COVID-19 psychosocial impacts across four groups: (a) non-Hispanic White (NHW) parents of children with asthma, (b) Black, Indigenous, or other People of Color (BIPOC) parents of healthy children, (c) BIPOC parents of children with asthma, and (d) NHW parents of healthy children (referent). The NIMHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…We created a scoring rubric for the COVID-19 Child Experience Survey (see Table 1; full rubric available in Appendix), as no rubric or psychometric data had been available for the original CASPE parent survey at the time of our study. Nonetheless, our scoring approach was similar to that of other recent studies making use of CASPE questionnaire items (34,35). Item scores were weighted more heavily depending on the severity of the event or experience, as determined via discussion and consensus from all authors.…”
Section: Child Emotion and Adaptive Behaviormentioning
confidence: 99%
“…We created a scoring rubric for the COVID-19 Child Experience Survey (see Table 1; full rubric available in Appendix), as no rubric or psychometric data had been available for the original CASPE parent survey at the time of our study. Nonetheless, our scoring approach was similar to that of other recent studies making use of CASPE questionnaire items (34,35). Item scores were weighted more heavily depending on the severity of the event or experience, as determined via discussion and consensus from all authors.…”
Section: Child Emotion and Adaptive Behaviormentioning
confidence: 99%
“…Parents in the present study had CEFIS Exposure and Impact scores comparable to a community sample described by Kazak et al, 2021 . Although disparate measures (e.g., Coronavirus Health and Impact Survey; Nikolaidis et al, 2021 ; COVID-19 Adolescent Symptom and Psychological Experience Questionnaire-Parent; Clawson et al, 2021 ) make it difficult to compare parents’ cumulative COVID-19-related experiences across studies, findings consistently suggest a high level of disruption in the lives of parents and families. In the present study, greater COVID-19 impacts were linked to higher levels of work-life conflict, greater stress when engaging in parent-assisted learning with their children, more feelings of parenting role overload, and elevated reports of anxiety and depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…37 Black, indigenous, people of color and non-Hispanic White parents of children with asthma were more concerned on resource losses and greater reduction in health care access when compared with non-Hispanic White parents of healthy controls. 38 In a postlockdown survey of children with asthma (ages 7 to 14) and their mothers (n = 45 dyads) compared with healthy control dyads, it was found that patients with asthma did not significantly differ from healthy peers in reporting psychological well-being (P =.18) and separation anxiety symptoms (P =.41). Children with asthma had normative functioning in a postlockdown period.…”
Section: Pediatric Asthmamentioning
confidence: 96%